Google Chrome OS: Cultural influence on product launch strategy between India and developed countries - Santhosh, Arjun (2011)
In recent times product launch has become vital deciding factor in the success of a product. The significance of product launch becomes even higher if the product is radically new and different from existing products in the market. The aim of this dissertation is to look into the possible factors which might influence the product launch of Google Chrome Operating System that has radical concepts and design. The essential variations which might be needed for the successful launch in India as compared to countries like United States of America, United Kingdom and Europe are researched. The focus of the study is on the cultural impact on consumer behaviour this will help in framing a better launch strategy. The research emphasises on the variables consumer behaviour, risk taking behaviour, preference formation for pioneer, acceptance of umbrella branding and brand positioning which influences launch strategies. Each of these variables is measured for India and developed countries; the difference is statistically analysed and discussed. The research finding will show the impact of culture on these variables and the impact of these variables on consumer behaviour. Recommendation of a launch strategy for Google Chrome OS in India is made by analysing these variables.